Mycoplasma lipoproteins are major determinants of neutrophil extracellular trap formation. (27th May 2016) - Cacciotto, Carla; Cubeddu, Tiziana; Addis, Maria F.; Anfossi, Antonio G.; Tedde, Vittorio; Tore, Gessica; Carta, Tania; Rocca, Stefano; Chessa, Bernardo; Pittau, Marco; Alberti, Alberto
Summary: Neutrophil granulocytes are paramount to innate responses as major effectors of acute inflammation. Among the various strategies enacted by neutrophils to eliminate microbes NETosis is a novel distinct antimicrobial activity in which an interlacement of chromatin fibres rich in granule‐derived antimicrobial peptides and enzymes is extruded (NETs, neutrophils extracellular traps ). NETs contribute to the pathogenesis of acute and chronic inflammatory disorders. The interactions of mycoplasmas and innate immune cells, in particular neutrophil granulocytes, are poorly defined. Here, we describe NET formation in vivo in the mammary gland and milk of sheep naturally infected by Mycoplasma agalactiae . Also, we assess the contribution of liposoluble proteins, the most abundant component of the Mycoplasma membrane, in inducing NETosis. We demonstrate that Mycoplasma liposoluble proteins induce NET release at levels comparable to what observed with other stimuli, such as lipopolysaccharides and phorbol 12‐myristate 13‐acetate. Stimulation of neutrophils with synthetic diacylated lipopeptides based on the M . agalactiae P48, P80, and MAG_1000 proteins, combined in a mix or used individually, suggests that NETosis might not be dependent on a specific lipopeptide sequence. Also, NETosis is partially abolished when TLR2 is blocked with specific antibodies. The results presented in this work provide evidences for the mechanisms underlying NET activation in mycoplasma infections, and on their contribution to pathogenesis of mycoplasmosis.